(untitled) (Bulletin of the International Association for Paleodontology, 2020)
Introduction: The ability to determine sex from unknown skeletal remains vital, and methods to do it on various bones of the human skeleton have been researched extensively. The present work consists in the analysis of coxal bones belonging to the victims of the 1755 Lisbon’s Earthquake. Aims: This project aims the characterization of the population whose skeletal remains were found in the Cloister’s South Wing of Academia das Ciências de Lisboa in 2004. Materials and Methods: In order to achieve the final objective, six measurements were taken, in anatomic position, and seven indices were calculated. Furthermore, morphological characteristics were observed through four different methods. These procedures were applied to a total number of 129 coxal bones. Results: From measurements and indices, the best results found were 16 females and 5 males, but the overall results were not reliable, since there was no consensus between the different measurements and so the majority of the coxal bone were classified as ambiguous. However, the Phenice’s Method in the study of the coxal morphology showed to be very specific – through this procedure 18 females and 9 males were estimated. Conclusions: It was noticed that the measurements and the calculation of indices are less reliable than the morphological observations. Moreover, Phenice’s Method seemed to be the most precise, once it evaluates three parameters simultaneously, instead of just one, allowing to obtain more accurate results for sexual discrimination.